Palmer Split Grafts for Defects of Palm, Fingers and Sole - S. C. Lodha; M. K. Harsha; A. M. Singhvi; C. K. Lohra (Indian Journal of Plastic Surgery)
The palm has proved to be the most satisfactory domor site for the defects of the palm, fingers and sole of the foot.